Modelling of optimal place for living in United Arab Emirates using geographical information system - Sultan Al Khaili, Saeed Mohammed (2013)
United Arab Emirate (UAE), in particular City of Abu Dhabi, is fast developing not only physically, economically and socially but also in other aspects of health, science and technology. Newly built skyscrapers, commercial/shopping centers, sport centers, modern housing and recreational centers are parts of the City‘s physical development. Despite this development there is a problem in selecting suitable places for renting a space for housing. Many factors could be considered in obtaining the optimal rental spaces since it is subjected to specific individual criteria and priorities. In this study, Geographical Information System (GIS) is used together with Decision Support System (DSS) and Analytical Hierarchy Process (AHP) to provide the user in the city with ability to view and select various form of rental spaces such as apartments or villas based on a set of criteria. First objective of this study is to define the spatial preferences in optimally selecting suitable space for rental based on literature review. Secondly is to determine spatial preferences for space rental selection through questionnaires survey. Final objective is to produce a Housing Preferences Model (HPM) using AHP and consequently to create spatial preference for rental space selection by using GIS. Results from this study could be used by potential tenant and housing consultant to locate initial suitable rental space while real estate agent and broker would be able to utilize it in selling, managing and promoting the properties. This study is also focusing on modelling GIS-DSS based on Points of Interest (POI) analysis for improving current housing selection practice, enhancing accuracy of housing selection and reducing searching cost. Results show that areas with higher POI attract more potential tenants and more houses are available for rental. Feedbacks from the questionnaires revealed that apartments are more preferable by tenants due to shorter distance to POI. Abu Dhabi inner city zone possess highest value of POI with higher spatial preferences for space rental compared to other zones. The results also depict that local residence prefer closer POI with minimum distance. Similar attitude is being observed amongst expatriate or foreigners in Abu Dhabi where closer to POI and amenities are always preferred in choosing space for rental.